One school for all or how inclusive education can succeed: Derivations from existential pedagogy (Pedagogical Horizons, 2019)
As part of the debate on the pros and cons of special needs schools Ernst Tatzer (2011) calls for "one special school for all". The following article explores the question of such a special school in which all children can learn together regardless of the differences between them. An approach to the answer takes place from the point of view of existential pedagogy. This comparatively young pedagogical approach is based on Viktor Frankl’s theory of meaning. The anthropological and philosophical assumptions of the Austrian psychiatrist have far-reaching implications for pedagogy and, ultimately, also give indications of the success factors of inclusive education.
Keywords: inclusive education, success factors, existential pedagogy, Viktor Frankl, phenomenological approach, pedagogical relation, focusing on answers, orientation towards potentials, personalised education, assessment